Struktur Pasar Komoditas Kentang Asal Batu di Malang Raya - Rahayu Relawati; Gumoyo Mumpuni Ningsih (Fakultas Pertanian, Universitas Timor, 2021)
Potato production in Batu City, East Java has increased but is not balance with the price stability received by farmers, due to market competition. This study purposed to analyze the structure of potato commodity market from Batu in Malang Raya (area includes Kota Malang, Kabupaten Malang, and Kota Batu). The sampling methods used were purposive sampling for determining potato farmers, and snowball sampling to determine traders along the marketing channel to follow the commodity flow of potato. The analysis of market structure includes market share, Concentration Ratio (CR4), and Herfindahl Hirchman Index. The results show that the market structure of potato commodities from Batu in Malang Raya is oligopoly market, which was identified from the market share, concentration ratio (CR) and Herfindahl Hirschman Index. The oligopoly market is known because the obtained CR4 value is between 20% - 80% and the value of IHH > 0.1. In this market structure farmers have a low bargaining position, whose position is as price taker. The recommendation given to increase the bargaining position of farmers is to shorten the marketing channels, for example by guiding farmers to do online marketing, so that they can have direct access to the end consumer. Further research needs to be done is analyzing the complete market structure of potato by using structure-conduct-performance approach and analysis of potato digital marketing.